EXPLORING HEALTH ASSISTANTS' EXPERIENCES WITH WORKPLACE VIOLENCE IN SAUDI HEALTHCARE SETTINGS - Zaid Fehaid Fahad Almutairi, Wanyan Fehaid Fahad Almutairi, Mudhahi Mashaab Moharq Almoharq, Saad Hamdan Ashawi Aldhafeeri, Abdulkarim Jaser Sabih Aldhafeeri, Meshal Barrak Dhayyaa Aldhafeeri (Chelonian Research Foundation, 2022)
Healthcare workplace violence, encompassing physical assault, verbal abuse, bullying, and threatening behaviors, poses substantial risks to provider safety and wellbeing globally. Frontline staff including health assistants face disproportionate violence from patients and visitors. However, minimal research exists exploring Saudi health assistants' experiences with workplace violence. This qualitative study aimed to address this gap by conducting individual semi-structured interviews with 25 health assistants regarding perspectives on workplace violence experiences, contributing factors, psychological impacts, and recommendations for improvement. Data underwent iterative inductive thematic analysis. Findings revealed frequent experiences of verbal harassment, threats, and intimidation from patients and visitors, with minimal physical violence reported. Key contributors were unauthorized entry and movement within facilities, long waiting times, and dissatisfaction with quality of care. Participants described impacts including fear, anxiety, frustration, anger, and trauma symptoms that accumulated over time and contributed to emotional exhaustion. Coping strategies encompassed avoiding provocative situations, venting to colleagues, and trying to empathize with perpetrators' frustrations. Participants also voiced needs for improved security enforcement, more stringent visitation policies, faster service, violence prevention training, post-incident debriefing, and greater organizational acknowledgement of violence effects on assistants. Overall, study findings provide novel insights into the disturbing yet common reality of workplace violence faced by Saudi health assistants and highlight priority areas for supportive organizational policies, protocols, training programs, and campaigns aimed at preventing violence and addressing deleterious impacts when events occur.